UJI TOKSISITAS AKUT KOMBINASI EKSTRAK BAWANG DAYAK (Eleutherine americana Merr.) DAN PINANG YAKI (Areca vestiaria Giseke) TERHADAP ORGAN PARU-PARU TIKUS PUTIH JANTAN GALUR WISTAR (Rattus norvegicus) - Khairunnisa Mutiara Thaib; Herny Simbala; Irma Antasionasti (PHARMACON, 2022)
Dayak onions (Eleutherine americana Merr.) and Pinang yaki (Areca vestiaria Giseke) have potential as traditional medicinal ingredients. However, the toxic effect of the combination of these extracts is not yet known. This study aimed to determine the effect of the combination of extracts Dayak and pinang yaki on the lungs of male white rats Wistar strain (Rattus norvegicus) in acute toxicity testing. This type of research was conducted using laboratory experimental methods consisting of 18 male white rats of wistar strains. Extraction was made by maceration using 96% Ethanol. The treatment was carried out for 14 days by observing body weight and macroscopic observations of the rat lungs. The results showed that the administration of combination extracts Dayak Onion and Pinang Yaki  for 14 days at dose of 10.8 mg, 14.4 mg, 21.6 mg didn’t cause any changed, on the macroscopic picture the lungs looked normal and didn’t different when compared with the control group. Based on the results of statistical tests in the combination treatment group proved  have a significant weight loss.